Florida Elder Abuse Survey in Seven Sites, 2007-2008 (United States) - Branch, Laurence G. ([Verlag nicht ermittelbar], 2010)
The purpose of this project was to develop and pilot test an interviewer-administered self-report questionnaire that might be used in a subsequent national survey to scientifically establish the prevalence of second-party elder abuse or neglect. The project focused only on those living in the communities who were capable of accurately self-reporting their knowledge, attitudes, and practices. Through focus groups of adult protective services and abuse hot-line staff, questionnaire items were generated and later tested through interviews of clients of aging services in Florida. Aging services case managers screened and recruited 95 clients, aged 65 and older, with 25 clients who had reports of mistreatment within the hotline database, and 70 comparison clients (no reports of mistreatment). Groups were matched by gender and age within 10 years. The interviews were conducted over an 18-month period, of which 3 interviews were conducted in-person and 92 interviews were conducted by telephone. All interviews were conducted by trained interviewers of the research team. Twenty-six interviews were conducted in Spanish. Interviews focused on demographics; activities of daily living; 19 possible types of elder abuse or neglect within the previous year, and, for each positive response, questions about the perpetrators and their relationship to the older adult; a description of when the mistreatment happened, how often, what the respondent did, and whether it was related to the perpetrator's anger, neglect, or carelessness.